2010
DOI: 10.1186/1476-069x-9-25
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral effects of transportation noise in primary schoolchildren: a cross-sectional study

Abstract: BackgroundDue to shortcomings in the design, no source-specific exposure-effect relations are as yet available describing the effects of noise on children's cognitive performance. This paper reports on a study investigating the effects of aircraft and road traffic noise exposure on the cognitive performance of primary schoolchildren in both the home and the school setting.MethodsParticipants were 553 children (age 9-11 years) attending 24 primary schools around Schiphol Amsterdam Airport. Cognitive performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 38 publications
6
56
1
Order By: Relevance
“…may be more sensitive concerning low intensity noises. Long term consequences and effects on well-being and health were demonstrated for children (Evans et al, 1995(Evans et al, , 1998van Kempen et al, 2010a;Matheson et al, 2003) and for adults (Elmenhorst et al, 2010) and have to be further examined in future investigations.…”
Section: Discussionmentioning
confidence: 91%
“…may be more sensitive concerning low intensity noises. Long term consequences and effects on well-being and health were demonstrated for children (Evans et al, 1995(Evans et al, , 1998van Kempen et al, 2010a;Matheson et al, 2003) and for adults (Elmenhorst et al, 2010) and have to be further examined in future investigations.…”
Section: Discussionmentioning
confidence: 91%
“…Children are often vulnerable to environmental noise and the reduction in exposure to this type of noise is an important public health issue. Results from several studies confirm that children living in a noisy environment have lower cognitive performance [6,7], show frequent reading problems [8,9], exhibit lower mathematical skills [10,11], and impaired memory [8,12]. It has also been shown that exposure to environmental noise may increase the prevalence of hypertension in the case of children [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 77%
“…At least 30% of the European Union (EU) population live in areas where day-night average of road traffic noise level exceeds 55 dB [18]. Thus, traffic-related noise is considered to be a factor of adverse health effects like: sleep disorders [19], annoyance [7,20], as well as chronic cortisol increase [21] and elevated level of systolic pressure among children [22]. The lack of available data describing potential sleep disorders related to the environmental noise among Polish children has prompted the authors to undertake this study.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to mental health, no direct association can be established due to operationalization difficulties basically, notwithstanding existing evidence for an apparent increased prevalence of anxiety and depression among residents living in airport surroundings (van Kamp & Davies, 2008). Most of the empirical works reviewed adjust their findings for socioeconomic and other health determinants, so this could be classified as an attempt to foster robustness of results.…”
Section: Implications For Transferability Of Values and Resultsmentioning
confidence: 99%